Disclosure of intellectual capital information of the airline companies in Malaysia - Noradiva Hamzah,; Zakiah Muhammaddun Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Despite the lack of structured reporting guideline for Intellectual Capital (IC) information, the information continues to be the stakeholders’ most preferred voluntary information. This article reports on an exploratory study that identifies important components of IC information included in corporate annual reports of two major airline companies in Malaysia. The level of disclosure is measured based on content analysis of their 2005 and 2006 annual reports. Findings reveal that both companies disclose all the three categories of the IC comprising the organisational, human and relational capital. Whilst both companies show increased level of disclosure when compared between 2005 and 2006, the level of disclosure for certain components differs between the two companies suggesting a need to regulate to get a more uniform disclosure. The finding also suggests that brand, intellectual property, personnel and partnerships are items of IC information prominently disclosed in the annual report of airline companies